2013
DOI: 10.1371/journal.pone.0053267
|View full text |Cite
|
Sign up to set email alerts
|

Growth Associated Protein 43 Is Expressed in Skeletal Muscle Fibers and Is Localized in Proximity of Mitochondria and Calcium Release Units

Abstract: The neuronal Growth Associated Protein 43 (GAP43), also known as B-50 or neuromodulin, is involved in mechanisms controlling pathfinding and branching of neurons during development and regeneration. For many years this protein was classified as neuron-specific, but recent evidences suggest that a) GAP43 is expressed in the nervous system not only in neurons, but also in glial cells, and b) probably it is present also in other tissues. In particular, its expression was revealed in muscles from patients affected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 46 publications
4
31
0
Order By: Relevance
“…In addition to its role in the SHH pathway, BOC is also a cell adhesion molecule with roles in proper myogenesis [Kang et al, 2002], making it a candidate for these phenotypes. GAP43 may play important roles in skeletal muscle development and function [Guarnieri et al, 2013], and mice lacking the orthologue demonstrated muscle incoordination, reduced strength, and altered reflexes, with heterozygotes demonstrating moderate impairments [Metz and Schwab, 2004]. Finally, the dopamine receptor Drd3 helps regulate spinal reflexes [Clemens and Hochman, 2004], so its deletion may contribute to the depressed reflexes observed.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its role in the SHH pathway, BOC is also a cell adhesion molecule with roles in proper myogenesis [Kang et al, 2002], making it a candidate for these phenotypes. GAP43 may play important roles in skeletal muscle development and function [Guarnieri et al, 2013], and mice lacking the orthologue demonstrated muscle incoordination, reduced strength, and altered reflexes, with heterozygotes demonstrating moderate impairments [Metz and Schwab, 2004]. Finally, the dopamine receptor Drd3 helps regulate spinal reflexes [Clemens and Hochman, 2004], so its deletion may contribute to the depressed reflexes observed.…”
Section: Discussionmentioning
confidence: 99%
“…The abrupt transition between the compressed and the extended zones in myofibrils is reminiscent of the local depolarization of mitochondria observed after the delivery by a microflow pipette of an uncoupling agent in a restricted region of the sarcolemma along a single dissociated muscle fiber (Bruton et al, 2014). These results suggest that the spacing of the actin- The model for the mouse skeletal muscle is modified from (Guarnieri et al, 2013), with mitochondria represented in red on both sides of the Z line, the sarcoplasmic reticulum in yellow. The blue compartment represents T-tubules.…”
Section: Flavin Tpef Microscopy Reveals Different Metabolic Changes Imentioning
confidence: 90%
“…Images were acquired using a Zeiss LSM510 META system (Jena, Germany) equipped with a Zeiss Axiovert 200 inverted microscope and a Plan Neofluar oil-immersion objective (40×). Negative controls for each immunostaining assay were performed by immunolabelling a sample with only the secondary antibody [35].…”
Section: Cellular Physiology and Biochemistry Cellular Physiology Andmentioning
confidence: 99%